Measuring ammonia emissions from land applied manure: an intercomparison of commonly used samplers and techniques - Misselbrook, T.H.; Nicholson, F.A.; Chambers, B.J.; Johnson, R.A. (Environmental pollution (1987), 2005)
A number of techniques have been developed to quantify ammonia (NH 3) emissions following land application of manure or fertiliser. In this study, coefficients of variation were determined for three commonly used field techniques (mass balance integrated horizontal flux, wind tunnels and the equilibrium concentration technique) for measuring emissions from a range of manure types. Coefficients of variation (CV) for absorption flasks, passive flux samplers and passive diffusion samplers were 21, 10 and 14%, respectively. In comparative measurements, concentrations measured using passive flux samplers and absorption flasks did not differ significantly, but those measured using passive diffusion samplers were on average 1.8 times greater. The mass balance technique and wind tunnels gave broadly similar results in two out of four field tests. Overexposure of passive diffusion samplers for some sampling periods meant that estimation of cumulative NH 3 emission using the equilibrium concentration technique in the field tests could not be made. For cumulative NH 3 emissions, CVs were in the range of 23–52, 46–74 and 21–39% for the mass balance, wind tunnel and equilibrium concentration techniques, respectively. Lower CVs were associated with measurements following slurry compared with solid manure applications. Our conclusions from this study are that for the measurement of absolute emissions the mass balance technique is to be preferred, and for small-plot comparative measurements the wind tunnel system is preferred to the equilibrium concentration technique. Three commonly used ammonia emission measurement techniques were compared for different manure types and gave CVs between 23 and 74%.